A New, Friendlier Methodology to Determine the Average Manganese Valence in LixMn2O4 Spinels Using Atomic Absorption Spectrometry and Molecular Absorption Spectrophotometry - Silva, Joao P. [UNESP]; Silva, Ricardo M. [UNESP]; Biaggio, Sonia R.; Bocchi, Nerilso; Rocha-Filho, Romeu C. (Soc Brasileira Quimica, 2018)
An alternative, friendlier methodology for the determination of the average manganese valence (nu) of manganese oxides (mainly pure and doped spinels) is presented. This methodology is based on the facile determination of the concentration of Mn2+ and Fe2+ ions by atomic absorption spectrometry (AAS) and molecular absorption spectrophotometry (MAS), respectively. Prior to this determination, the manganese oxides are reacted with an acidic solution containing Fe2+ ions, when all Mn nu+ ions are reduced to Mn2+. Then, the concentration of Mn2+ ions is obtained directly by AAS, whereas that of Fe2+ ions is obtained by MAS after their complexation with o-phenanthroline. Using this methodology, the obtained mean (n = 3). values for the stoichiometric oxides Mn2O3 and Mn3O4 are 2.98 +/- 0.01 and 2.66 +/- 0.01, respectively; their precision is a clear evidence of the suitability of the here-proposed methodology. Additionally, a precise mean. value (3.46 +/- 0.01; n = 3) is also obtained for the spinel Li1.05Mn2O4, whereas a higher. value (3.52 and 3.53; n = 2) is obtained for the doped spinel Li1.05Mn1.98Al0.02O3.98S0.02, evidencing that effective doping has been indeed attained. This novel methodology is easily applicable for Mn oxides in electrode materials of many energy storage devices.
Keywords: manganese oxides; Mn valence spectroscopic determination; Li1.05Mn2O4 spinel; doped spinel Li1.05Mn1.98Al0.02O3.98S0.02